2014
DOI: 10.1111/cei.12540
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pooled human immunoglobulins in an animal model of neuromyelitis optica with chronic application of autoantibodies to aquaporin 4

Abstract: Neuromyelitis optica (NMO) is a relapsing, chronic inflammatory disease of the central nervous system (CNS) mainly affecting the spinal cord and the optic nerves. The discovery of highly specific associated autoantibodies (AB) to the osmotic-driven water channel aquaporin 4 (APQ4) led to the classification of NMO as a separate entity from multiple sclerosis [1,2]. AQP4 is an integral membrane protein, located on the abluminal side of astrocyte endfeet in the CNS. Immunopathology of typical NMO lesions show dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
1
0
0
Order By: Relevance
“…AQP4 antigen specificity was demonstrated by the absence of the effect of the control IgG and the dramatic decrease of the effect in AQP4-IgG-depleted IgG. Our study thus validates a concept that has been already suggested in NMO by several in vitro studies [ 12 14 , 24 ] and in animal models based on passive transfer of AQP4-IgG in the periphery [ 33 ] or iterative injection of AQP4-IgG directly into the spinal cord [ 21 , 34 ]. There are accumulative evidences for such intrinsic effect of autoantibody against surface antigens in other antibody-mediated CNS disorders.…”
Section: Discussionsupporting
confidence: 85%
“…AQP4 antigen specificity was demonstrated by the absence of the effect of the control IgG and the dramatic decrease of the effect in AQP4-IgG-depleted IgG. Our study thus validates a concept that has been already suggested in NMO by several in vitro studies [ 12 14 , 24 ] and in animal models based on passive transfer of AQP4-IgG in the periphery [ 33 ] or iterative injection of AQP4-IgG directly into the spinal cord [ 21 , 34 ]. There are accumulative evidences for such intrinsic effect of autoantibody against surface antigens in other antibody-mediated CNS disorders.…”
Section: Discussionsupporting
confidence: 85%